Hubungan status besi dan ioidum ibu hamil trimester III terhadap berat badan dan lingkar kepala bayi lahir didaerah endemik GAKI - Novitasari, Sherly; Hadisaputro, Soeharyo; SS, Darmono; Rachmawati, Banundari; Pemayun, Tjokorda Gde Dalem (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2016)
Background: Iodine and iron were micronutrient that highly related with formation of thyroid hormone. Iodine and iron deficiency during pregnancy, will affect fetal development. Weight and born baby’s head circumference were early indicator of infant development, because it describe the result of interaction of several factors for fetus during pregnancy. Objectives: To determine correlation between iodine and iron status of pregnant women in third trimester with born baby’s weight and head circumference. Methods: Cross sectional study with 49 pregnant women on third trimester and their baby born. Measurement of iron status used sTfR level by ELISA and iodine status used EIU. Meanwhile for the born baby, measurement was taken place on the baby’s weight and head circumference. Results: The average of iron status is 22,15 nmol/L, meanwhile average of iodine status is 168,63 μg/L with urine median value 165 μg/L. Statistical analysis with multiple correlation test showed no significant relationship between iron and iodine status of third trimester pregnant women to birth weight (r = 0,286; p = 0,141) as well as the babies head circumference (r = 0,195; p = 0,412).Conclusion: Iron and iodine status of third trimester pregnant women have low correlation to the born babies weight or head circumference in endemic area.